Nano and Microparticle Emerging Strategies for Treatment of Autoimmune Diseases: Multiple Sclerosis and Type 1 Diabetes. Issue 11 (27th April 2020) - Kwiatkowski, Alexander J.; Stewart, Joshua M.; Cho, Jonathan J.; Avram, Dorina; Keselowsky, Benjamin G.
Abstract: Autoimmune diseases affect 10% of the world's population, and 1 in 200 people worldwide suffer from either multiple sclerosis (MS) or type 1 diabetes (T1D). While the targeted organ systems are different, MS and T1D share similarities in terms of autoreactive immune cells playing a critical role in pathogenesis. Both diseases can be managed only symptomatically without curative remission, and treatment options are limited and non‐specific. Most current therapies cause some degree of systemic immune suppression, leaving the patients susceptible to opportunistic infections and other complications. Thus, there is considerable interest in the development of immunotherapies not associated with generalized immune suppression for these diseases. This review presents current and preclinical strategies for MS and T1D treatment, emphasizing those aimed to modulate the immune response, including the most recent strategies for tolerance induction. A central focus is on the emerging approaches using nano‐ and microparticle platforms, their evolution as immunotherapeutic carriers, including those incorporating specific antigens to induce tolerance and reduce unwanted generalized immune suppression. Abstract : This work reviews current literature on the treatment of the autoimmune diseases multiple sclerosis (MS) and type 1 diabetes (T1D), specifically focusing on nano‐ and microparticle (NMP) treatments. The article begins by outlining treatments currently used in the clinic, and moves to NMP treatments, with attention paid to antigen‐specific treatments.